FERTILIZAÇÃO ORGÂNICA VIA FOLIAR NO DESENVOLVIMENTO INICIAL DE EUCALIPTO EM SISTEMA SILVIPASTORIL - Kelly Oliveira Perdomo, Brena; Eduarda Oliveira Juvêncio , Maria; Feliciani Barbosa , Giselle (ANAIS DO ENIC, 2026)
-